Anticancer Effects of Palladium Complexes of Dithiocarbamate Derivatives on Esophageal Cancer Cell Line (KEYSE-30) - Nowruz Najafzadeh; Sharam Hadizadeh; Mohammad Mazani; Mojtaba Amani; Hassan Mansouri Torshizi (مجله دانشکده پزشکی اصفهان, 2014)
Background: Surgery, radiation therapy, drug therapy or a combination of these methods can be used for the treatment of malignancies. Drug therapy in cancer includes chemotherapy, biotherapy and use of monoclonal antibodies against antigens of malignant cells. Heavy metal complexes are of the compounds used as drugs in chemotherapy against malignant cells. The present study aimed to assess the effects of new anticancer palladium complexes on esophageal cancer cells.